A Network Pharmacology Study to Explore the Underlying Mechanism of Safflower (Carthamus tinctorius L.) in the Treatment of Coronary Heart Disease. (14th May 2022) - Meng, Qingwen; Liu, Huajiang; Wu, Haolin; shun, Ding; Tang, Chaoling; Fu, Xinyin; Fang, Xingyue; Xu, Yiqian; Chen, Bocen; Xie, Yiqiang; Liu, Qibing
Abstract : Safflower has long been used to treat coronary heart disease (CHD). However, the underlying mechanism remains unclear. The goal of this study was to predict the therapeutic effect of safflower against CHD using a network pharmacology and to explore the underlying pharmacological mechanisms. Firstly, we obtained relative compounds of safflower based on the TCMSP database. The TCMSP and PubChem databases were used to predict targets of these active compounds. Then, we built CHD-related targets by the DisGeNET database. The protein-protein interaction (PPI) network graph of overlapping genes was obtained after supplying the common targets of safflower and CHD into the STRING database. The PPI network was then used to determine the top ten most significant hub genes. Furthermore, the DAVID database was utilized for the enrichment analysis on Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). To validate these results, a cell model of CHD was established in EAhy926 cells using oxidized low-density lipoprotein (ox-LDL). Safflower was determined to have 189 active compounds. The TCMSP and PubChem databases were used to predict 573 targets of these active compounds. The DisGeNET database was used to identify 1576 genes involved in the progression of CHD. The top ten hub genes were ALB, IL6, IL1B, VEGFA, STAT3, MMP9, TLR4, CCL2, CXCL8, and IL10 . GO functional enrichment analysis yielded 92 entries for biological process (BP), 47 entries for cellular component (CC), 31 entries for molecular function (MF), and 20 signaling pathways, which were obtained from KEGG pathway enrichment screening. Based on these findings, the FoxO signaling pathway is critical in the treatment of CHD by safflower. The in vitro results showed that safflower had an ameliorating effect on ox-LDL-induced apoptosis and mitochondrial membrane potential. The western blot results showed that safflower decreased Bax expression and acetylation of FoxO1 proteins while increasing the expression of Bcl-2 and SIRT1 proteins. Safflower can be used in multiple pathways during CHD treatment and can exert anti-apoptotic effects by regulating the expression of Bax, Bcl-2, and SIRT1/FoxO1 signaling pathway-related proteins.